Genetic and Epigenetic Regulation of the Brain-Derived Neurotrophic Factor in the Central Nervous System - Martínez-Levy, Gabriela A. (YJBM, 2014)
The BDNF is required for the development and proper function of the central nervous system, where it is involved in a variety of neural and molecular events relevant to cognition, learning, and memory processes. Although only a functional mature protein is synthesized, the human BDNF gene possesses an extensive structural complexity, including the presence of multiple promoters, splicing events, and 3´UTR poly-adenylation sites, resulting in an intricate transcriptional regulation and numerous messengers RNA. Recent data support specific cellular roles of these transcripts. Moreover, a central role of epigenetic modifications on the regulation of BDNF gene transcription is also emerging. The present essay aims to summarize the published information on the matter, emphasizing their possible implications in health and disease or in the treatment of different neurologic and psychiatric disorders.